The U.S. training institute for dissemination and implementation research in health - Meissner Helen I; Glasgow Russell E; Vinson Cynthia A; Chambers David; Brownson Ross C; Green Lawrence W; Ammerman Alice S; Weiner Bryan J; Mittman Brian (Implementation Science, 2013)
Abstract Background The science of dissemination and implementation (D&I) is advancing the knowledge base for how best to integrate evidence-based interventions within clinical and community settings and how to recast the nature or conduct of the research itself to make it more relevant and actionable in those settings. While the field is growing, there are only a few training programs for D&I research; this is an important avenue to help build the field’s capacity. To improve the United States’ capacity for D&I research, the National Institutes of Health and Veterans Health Administration collaborated to develop a five-day training institute for postdoctoral level applicants aspiring to advance this science. Methods We describe the background, goals, structure, curriculum, application process, trainee evaluation, and future plans for the Training in Dissemination and Implementation Research in Health (TIDIRH). Results The TIDIRH used a five-day residential immersion to maximize opportunities for trainees and faculty to interact. The train-the-trainer-like approach was intended to equip participants with materials that they could readily take back to their home institutions to increase interest and further investment in D&I. The TIDIRH curriculum included a balance of structured large group discussions and interactive small group sessions. Thirty-five of 266 applicants for the first annual training institute were accepted from a variety of disciplines, including psychology (12 trainees); medicine (6 trainees); epidemiology (5 trainees); health behavior/health education (4 trainees); and 1 trainee each from education & human development, health policy and management, health services research, public health studies, public policy and social work, with a maximum of two individuals from any one institution. The institute was rated as very helpful by attendees, and by six months after the institute, a follow-up survey (97% return rate) revealed that 72% had initiated a new grant proposal in D&I research; 28% had received funding, and 77% had used skills from TIDIRH to influence their peers from different disciplines about D&I research through building local research networks, organizing formal presentations and symposia, teaching and by leading interdisciplinary teams to conduct D&I research. Conclusions The initial TIDIRH training was judged successful by trainee evaluation at the conclusion of the week’s training and six-month follow-up, and plans are to continue and possibly expand the TIDIRH in coming years. Strengths are seen as the residential format, quality of the faculty and their flexibility in adjusting content to meet trainee needs, and the highlighting of concrete D&I examples by the local host institution, which rotates annually. Lessons learned and plans for future TIDIRH trainings are summarized.